2021
DOI: 10.1109/access.2021.3072969
|View full text |Cite
|
Sign up to set email alerts
|

A Demand-Supply Matching-Based Approach for Mapping Renewable Resources Towards 100% Renewable Grids in 2050

Abstract: Recently, many renewable energy (RE) initiatives around the world are based on general frameworks that accommodate the regional assessment taking into account the mismatch of supply and demand with pre-set goals to reduce energy costs and harmful emissions. Hence, relying entirely on individual assessment and RE deployment scenarios may not be effective. Instead, developing a multifaceted RE assessment framework is vital to achieving these goals. In this study, a regional RE assessment approach is presented ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…During the times of higher temperatures, the upward movement of air continues to reduce the velocity difference at the two heights of 20 m and 34 m AGL due to the bunching of streamlines and acceleration of flow at lower heights, which is clear from the figure. In their work on mapping renewable sources for 100% renewable grids in 2050, Al-Ghussain, et al [58] made their estimates with a wind shear coefficient of 1/7.…”
Section: B Wind Shear Analysismentioning
confidence: 99%
“…During the times of higher temperatures, the upward movement of air continues to reduce the velocity difference at the two heights of 20 m and 34 m AGL due to the bunching of streamlines and acceleration of flow at lower heights, which is clear from the figure. In their work on mapping renewable sources for 100% renewable grids in 2050, Al-Ghussain, et al [58] made their estimates with a wind shear coefficient of 1/7.…”
Section: B Wind Shear Analysismentioning
confidence: 99%
“…Thus, there is a universal intention to reduce the harmful environmental impacts of electricity production [4]. Recent investigations have demonstrated that if energy consumption stays at the same rate, fossil fuel reserves will be depleted in the next 50-60 years [5]. For this reason, the necessity for a more efficient method of connection between electricity generation and the consumers is highly apparent.…”
Section: Energy Management In Distribution Systemsmentioning
confidence: 99%
“…Besides, the right-handed part of the power balance equation is defined by load demands located at buses of the networked microgrid system. The power generation related to each unit is expressed in detail by Equations ( 3)- (5). The output power of PV units can be calculated by Equation (3) which complies with relevant PV capacity, the sun irradiation and the power loss consumed by cells.…”
Section: Formulation Definition Of the Proposed Frameworkmentioning
confidence: 99%
“…The proposed system to co-generate electricity and hydrogen consists of the components demonstrated in Table 1. In addition, some postulations, which are presented in the table below, should be taken into account in order to attain the purpose of the study [54][55][56][57]. Figure 2 presents the average electric load demanded by the 15 households in the under-study village on a monthly and hourly basis.…”
Section: Assumptionsmentioning
confidence: 99%